TO COMMUNICATIVE COMPETENCE IN MARITIME ENGLISH THROUGH PROFESSIONAL IDENTIFICATION - Ohorodnyk , Natalia (Studies in Comparative Education, 2024)
The article presents the findings of a research study on the relationships between the processes of future seafarers' professional identity formation and their professional English-language communicative competence development. The process of professional identity formation is characterized by evolutionary changes, which can be observed through the lens of the communicative component. These changes can be identified as actions that establish a professional communicative identity, which in turn have a direct impact on the communicative competence of future specialists. The process of professional identification for future seafarers consists of three stages. In Stage I, Adaptation, cadets face a period of adjustment as they enter a new social and professional environment, confronting the realities of their career choice and beginning to form their professional identity. Stage II, Stabilization, involves the cadets becoming more comfortable in their roles, with an emphasis on professional training and early specialization. In Stage III, Correction, cadets engage in extended seagoing practices that deepen their professional interests and further solidify their commitment to their chosen career in maritime transport.